Enhance or inhibit? Unveiling the influence of chairman’s hometown attachment on the corporate philanthropy–Corporate financial performance relationship - Chen, Limin; Bu, Xuelin (Frontiers in Psychology, 2022)
Although there have been numerous studies on the relationship between corporate philanthropy and corporate financial performance (CFP), theoretical analysis focusing on the legitimacy-based mechanism and the moderating role of key executives' psychological characteristics is scarce. Hometown attachment is a special form of place attachment in environmental psychology, which reflects people's psychological attachment to their hometown and the state of maintaining an intimate emotional connection with it. Based on Scott's three-pillar institutional perspective, this paper traces its origins from the Chinese cultural context, and discusses the legitimacy basis of donations in the Chinese cultural context and why donations can improve CFP. On this basis, the moderating effect of the chairman's hometown attachment on the corporate donation-performance relationship is empirically tested. Through logical deduction, hometown attachment may form legitimacy pressure to weaken the above relationship or leverage more legitimacy resources to strengthen such a relationship. Which effect dominates? The empirical results in this paper of A-share listed firms from 2009 to 2018 show that the moderating role of hometown attachment is more in line with the resource theory than the former pressure theory. Further research shows that the government and consumers are important providers of these legitimacy resources. This study reveals the mechanism for legitimacy acquisition through corporate donations in the Chinese context and answers the question of what the chairman's hometown attachment brings about to their donation performance, providing some inspiration for practice.